Quantitative reconstruction of eutrophication histories in central Mexican lakes - Hill, Emma Louise (2006)
The primary aim of this study was to develop a diatom based nutrient transfer function for central México, and apply it to a sediment core from Laguna Zirahuén, Michoacán Mexico, (19⁰ 26' N, 101⁰ 44' W) reconstruct change in nutrient availability over the last ca. 200 years. The principle techniques employed were analysis of diatoms, stable isotopes of carbon and nitrogen and lipid biomarkers. These were supplemented by magnetic susceptibility and isotopic measurements of modern aquatic and terrestrial organic matter. In order to interpret the diatom record and quantitatively reconstruction the change in the diatom flora a calibration data set, from 30 lakes, was collected during both the wet and the dry seasons.